참여학습과 관찰학습의 실습만족도 및 임상수기술 - 신은주; Eun Ju Shin (동의신경정신과학회지, 2008)
Objective: The purpose of this study was to compare satisfaction of practice and clinical skill in different participation learning and observation learning, and to offer the basic data to promote quality of nursing education. Method: The study used a quasi-experimental, nonequivalent control group post-test design. The subjects were 62 nursing students of K college in Jeonbuk, and the period of data gathering was limited from 19 Nov. 2006 to 30 Nov. 2006. Experience group was taught by hand-on education and control group was taught by conventional education. The instrument tools included self-efficacy, satisfaction of practice and clinical skill. The collected data were analyzed by SPSS-PC programme. Result: The results of this study were as follows: There was statistically a significance difference between the two group about satisfaction of practice(t=2.011 p=.043), and clinical skill(t=11.997, p=.000). Self-efficacy showed a significantly positive correlation with satisfaction of practice(r=.476, p=.000) and clinical skill(r=.178, p=.014). Also, satisfaction of practice showed a significantly positive correlation with clinical skill(r=.182, p=.007). Conclusion: In conclusion, this study suggests that hand-on education is an effective learning method to nursing students. By utilizing hand-on education, makes nursing students plan self-directed nursing performance and improve their clinical skills.